Tree Growth and Accumulation of Organic Carbon and Nutrients in Soil Under Tree Plantations in Arid Zone of Punjab - Singh, Baljit; Sharma, K. N. (Indian Forester, 2012)
Litterfall added by trees enriches the organic matter and nutrient content of soil under the trees. The influence of tree species was evaluated on soil organic carbon (OC), available macro (N, P and K) and micronutrient (Zn, Fe, Mn and Cu) concentration of soil and their accumulation in the soil under 8 year old Eucalyptus tereticonis (eucalyptus), Azadirachta indica (neem), Mella azedarach (dek), Dalbergia sissoo (shisham), Albizia lebbeck (siris), Leucoena leucocephala (subabul), Acacia nilotica (kikar) and Tamarix articulata (farmah) spaced at 6 Ã— 3 m and adjoining open (control) in arid zone area of Punjab at Regional Research Station of Punjab Agricultural University (PAU) at Bathinda. Siris and eucalyptus attained more diameter at breast height and height than other tree species. The concentration and accumulation of soil OC and available nutrients were higher under trees than control. The soil OC and nutrient concentration decreased with increase in depth. Soli OC increased by 50.3% under siris followed by shisham (43.4%) and kikar (40.6%) over control (3.62 g/kg) in the surface soil layer. The OC sequestration in the 0-120 cm soil depth varied from 37.1 Mg/ha under eucalyptus to 42.2 Mg/ha under shisham. The available N concentration was higher under subabul, shisham, kikar and siris than the other tree species in the surface as well as in 0-120 cm soil depth. Available P and K were higher under kikar and subabul than other tree species. All the micronutrients were higher under the tree species as compared to control. Thus, the tree plantations can sustain the soil health by improving the different soil properties.